Enhancing students’ scientific attitudes with a problem-based learning model integrated green chemistry - Putri, Sarmila Eka; Aznam, Nurfina (Pascasarjana Universitas Negeri Medan, 2024)
Enhancing scientific attitudes through education by incorporating green chemistry principles is essential, so that students can explore new ideas and information about chemistry concepts while considering environmental sustainability. This has the potential to change chemistry learning to be more meaningful. This study aims to determine the influence of the problem-based learning (PBL) model integrated with green chemistry on students' scientific attitudes. This research is a quasi experiment research with pretest-posttest control group design. The participants were XI MIPA class students who were randomly selected. The data collection method used scientific attitude questionnaire as an instrument. Data analysis includes n-gain test and hypothesis testing using t test. The results showed a sig value of 0.000 (0.000 < 0.05) and tcount of 5.136 (tcount > ttable). This indicates that there is a significant difference in scientific attitudes between students who follow the PBL-green chemistry learning model and students who follow learning with a scientific approach. The existence of this difference indicates that the PBL-green chemistry model has a positive influence in improving students' scientific attitudes.